Environmental science : - Enger, Eldon D. (McGraw-Hill Higher Education, 2010)
This full-color, introductory environmental science text is known for being concise, conceptual, and value-priced. The approach and reading level cover the basic concepts without overloading students with too much detail. The authors reinforce the text's central theme of "interrelationships" by providing a historical perspective, information on economic and political realities, discuss the role of different social experiences, and integrate this with the crucial science to describe the natural world and how we affect it.